Agenda for change : need for law reform / edited by Bibek Debroy - Rajiv Gandhi Institute for Contemporary Studies (New Delhi, 1999)
This collection of essays sheds light on aspects of this and other problems. The essays are penned by experts. The first part of the volume consists of essays that cover the broad canvas of law reform. The second deals with labour market reforms, an important part of the larger field of law reform. These essays do not claim to cover the entire gamut of issues, but if discussion can be stimulated, the aim of publishing this work will have been accomplished.
Keywords: Law reform